Gender Differences in Publication Productivity, Academic Rank, and Career Duration Among U.S. Academic Gastroenterology Faculty. (August 2016) - Diamond, Sarah J.; Thomas, Charles R.; Desai, Sima; Holliday, Emma B.; Jagsi, Reshma; Schmitt, Colleen; Enestvedt, Brintha K.
Abstract : Purpose: Female representation in academic medicine is increasing without proportional increases in female representation at senior ranks. The purpose of this study is to describe the gender representation in academic gastroenterology (GI) and compare publication productivity, academic rank, and career duration between male and female gastroenterologists. Method: In 2014, the authors collected data including number of publications, career duration, h-index, and m-index for faculty members at 114 U.S. academic GI programs. Results: Of 2, 440 academic faculty, 1, 859 (76%) were men and 581 (24%) were women. Half (50%) of men held senior faculty position compared with 29% of women ( P < .001). Compared with female faculty, male faculty had significantly ( P < .001) longer careers (20 vs. 11 years), more publications (median 24 [0–949] vs. 9 [0–438]), and higher h-indices (8 vs. 4). Higher h-index correlated with higher academic rank ( P < .001). The authors detected no difference in the h-index between men and women at the same rank for professor, associate professor, and instructor, nor any difference in the m-index between men and women (0.5 vs. 0.46, respectively, P = .214). Conclusions: A gender gap exists in the number and proportion of women in academic GI; however, after correcting for career duration, productivity measures that consider quantity and impact are similar for male and female faculty. Women holding senior faculty positions are equally productive as their male counterparts. Early and continued career mentorship will likely lead to continued increases in the rise of women in academic rank.